Cytotoxic effect of clinacanthus nutans semi-purified fraction (SF1) in combination with cisplatin against human cervical cancer - Nur Fatin Najihah Marzuki,; Yusmazura Zakaria,; Maryam Azlan,; Nik Fakhuruddin Nik Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Cervical cancer is one of the most diagnosed malignancies in the world, and it is associated with HPV virus infection and invasion. A standard fraction from the medicinal plant Clinacanthus nutans was successfully separated, isolated, and identified as SF1 (semi-purified fraction). According to the previous study, SF1 has shown cytotoxic action against the cervical cancer cell line, SiHa. This study aims to further annotate the effect of SF1 in combination with cisplatin against SiHa to increase the selectivity of the anti-cancer treatment. The MTT assay was used to analyse the combination treatment’s cytotoxicity, and its index value was calculated using the Chou-Talalay method. A cell survival test was conducted to evaluate the reproducibility of cancer cells after being treated. The combination treatment has enhanced cytotoxic action and inhibited SiHa’s cell proliferation the most (IC50 value = 5.10 ± 0.86 μg/mL) compared to the individual cytotoxic activity of SF1 (IC50 value = 9.60 ± 0.20 µg/mL) and cisplatin (IC50 value = 3.60 ± 0.60 μg/mL). Simultaneously, the combination study has shown lesser cytotoxic activity towards normal cells, Vero (IC50 value = 10.30 ± 3.10 μg/mL) compared to SiHa cells. The combination also showed an antagonism effect with CI values of 2.60 to 1.50 and fractional inhibition (Fa) of 0.50 to 0.90. The findings have demonstrated that in contrast with single-agent therapy, the treatment of SF1 and cisplatin in combination has increased the efficacy because it selectively targets cancer cells by antagonism action.